Meningkatkan Kreatifitas Melalui Metode Discovery Learning Fase E Kelas X di SMAN 2 Ruteng Purang - Maria Melania Mendi (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This research was conducted at SMAN 2 Ruteng-Purang in Class X-E which aims to improve students' creativity in Catholic religious subjects through the Discovery Learning method. The method used in this study is Classroom Action Research (CAR). This study consists of two cycles, each cycle is carried out in two meetings. The subjects in this study were 34 students of class X-E SMAN 2 Ruteng-Purang. Data collection techniques are carried out by observation and tests aimed at measuring students' abilities in learning, data analysis with percentage formulas. The results of the study obtained after the application of the Discovery Learning model showed a significant increase in student creativity in learning Catholic Religion.